2018
DOI: 10.1108/ijoem-03-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Institutional dysmorphia: when the institutions become ill

Abstract: Purpose The purpose of this paper is to discuss the influence of SOEs on institutions. The authors argue that in some cases there are differences in institutional shape between the shape that is actually demanded by an institution’s institutional environment and the shape that the institution itself believes is demanded of its institutional framework. The authors observed a behavior specific to institutions that change their institutional shape in response to demands, irrespective of whether these demands are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…Formal institutions relate to the functioning of regulatory institutions such as constitutions, laws, property rights and governmental regulations (Mair et al , 2012). Formal institutions may guide institutional mimetic isomorphism (DiMaggio and Powell, 1983) or a firms’ emulation of another firm’s best-practice as a means to increase legitimacy (Monticelli et al , 2018). Therefore, isomorphism may lead to convergent CSR behavior from companies sharing the same business context, whether they are conventional or Islamic organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Formal institutions relate to the functioning of regulatory institutions such as constitutions, laws, property rights and governmental regulations (Mair et al , 2012). Formal institutions may guide institutional mimetic isomorphism (DiMaggio and Powell, 1983) or a firms’ emulation of another firm’s best-practice as a means to increase legitimacy (Monticelli et al , 2018). Therefore, isomorphism may lead to convergent CSR behavior from companies sharing the same business context, whether they are conventional or Islamic organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that despite the introduction of new rules-based policies for SCRM, traditional relational and embedded networks shape CSC's institutional environment via distinct but interlinked neo-institutional pressures for risk analysis, identification, and treatment in state and private CSC. More so, the study advances a theoretical framework for the different neo-institutional cycles of SCRM that give rise to institutional dysmorphia between state-owned and private firms, as described by Monticelli et al (2018).…”
Section: Managerial and Theoretical Contributionsmentioning
confidence: 92%
“…In addition to the institutional pressures that characterize actors' risk behaviors in an organizational field, governments' elite interests also contribute to institutional isomorphism (DiMaggio and Powell, 1983). In this regard, Monticelli et al (2018) found that firms in volatile or transition economies display a form of institutional dysmorphia by selecting markedly different management strategies from their counterparts in stable and regulated economies. China's expanding hegemony in the global construction sector provides an exciting context to explore the impact of neoinstitutionalism on the SCRM strategies used in global construction projects (Morck et al, 2008;Olson and Wu, 2011).…”
Section: [Insert Table 1 About Here]mentioning
confidence: 99%
See 1 more Smart Citation
“…From an international business perspective, for example, institutions in emerging markets have been shown to affect foreign direct investment (Barnard & Luiz, 2018;Buckley, Chen, Clegg, & Voss, 2018;Gaur, Ma, & Ding, 2018;Iammarino, 2018;Mahembe & Odhiambo, 2016;Wang & Li, 2018), corruption (Luiz & Stewart, 2014;Puffer, McCarthy, & Jaeger, 2016;Rabbiosi & Santangelo, 2018;Sartor & Beamish, 2018), the execution of business models (Urban & Hwindingwi, 2016), the nature and management of political risk (Giambona, Graham, & Harvey, 2017), innovation (Newburry, McIntyre, & Xavier, 2016;Peng, Ahlstrom, Carraher, & Shi, 2017); and the behavior of firms more generally within an international business context (Doh, Rodrigues, Saka-Helmhout, & Makhija, 2017;Luiz & Ruplal, 2013;Luiz, Stringfellow, & Jefthas, 2017;Meyer & Peng, 2016), amongst other impacts. It is therefore important for us to fully grasp the long-run, potentially deterministic, consequences of good or bad institutions, (Jackson & Deeg, 2019;Monticelli et al, 2018) on developing and emerging markets because vast parts of the world are going to be experiencing significant transitions (both political and economic) in the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%